МОДЕЛЮВАННЯ АНІЗОТРОПІЇ ПИТОМОЇ ЕЛЕКТРОПРОВІДНОСТІ БІОЛОГІЧНОЇ ТКАНИНИ, ЯКА ВИНИКАЄ ЗА ЛОКАЛЬНОГО СТИСКАННЯ ЕЛЕКТРОДАМИ ДЛЯ БІПОЛЯРНОГО ЗВАРЮВАННЯ - Ланкін, Ю.М.; Соловйов, В.Г.; Романова, І.Ю. (Інститут електродинаміки НАН України, Київ, 2021)
Current publications on bipolar welding use the electrical characteristics of uncompressed biological tissue. This reduces the accuracy of calculating the distribution of the density of the flowing currents and the strength of the electric fields in the zone of the fabric to be welded when it is squeezed. The aim of the work is to show a methodology for calculating the change in the specific electrical conductivity of biological tissue under local compression by electrodes and the effect of this factor on the results of modeling electrical processes of biological welding. A geometric interpretation of the change in the electrical conductivity of the pig's heart muscle when squeezed by bipolar welding electrodes in relative units is proposed. The principle of similarity of the geometric parameters of the physical experiment and the graphic model of COMSOL multyphysics is used, as a result of which the dependences of the three main geometric parameters of the model on the magnitude of the relative compression are determined. The method of successive approximations of the values of the total electrical resistance of biological tissue in a physical experiment at frequencies of 0,3, 30, and 300 kHz and the calculated resistances on the model with a change in the basic geometric parameters of specific electrical conductivity was used. A model of bipolar welding of biological tissues is obtained, which takes into account the anisotropy factor of the electrical conductivity of biological tissue under compression. Some results of investigations of the regularities of the current flow in the tissue, taking into account the arising anisotropy, are presented. References 12, figures 5, tables 4.